Kriptografi dan Penerapannya Dalam Sistem Keamanan Data - Nanda Amalya Nanda; Santa Maria Sopiana Silalahi; Della Fatricia Nasution; Melia Sari; Indra Gunawan (Jurnal Media Informatika, 2023)
An understanding of what cryptography is, to understand cryptography and how it is applied in data security, so that data will be safer and more protected from spamming or illegal hacking of information. Observations of cryptography and its application to data security are carried out using the Approach of Literary Studies. Library Studies is a data collection technique by studying various reference books and the results of previous similar research, which is useful for obtaining a theoretical foundation on the problem to be studied. Cryptography is a technique of conveying messages in a hidden manner by utilizing data encryption features, which serve to secure data, whether transferred through a computer network or not, which is very useful for protecting, privacy, data integrity, authentication, and non-repudiation. Nowadays the use of cryptography has begun to be widely used in everyday life. Use cryptographic systems for the security of your data when accessing information.